Environmental changes affect the microbial release of hydrogen sulfide and methane from sediments at Boknis Eck (SW Baltic Sea) - Perner, Mirjam; Wallmann, Klaus; Adam-Beyer, Nicole; Hepach, Helmke; Laufer-Meiser, Katja; Böhnke, Stefanie; Diercks, Isabel; Bange, Hermann W.; Indenbirken, Daniela; Nikeleit, Verena; Bryce, Casey; Kappler, Andreas; et al. (Frontiers in Microbiology, 2022)
Anthropogenic activities are modifying the oceanic environment rapidly and are causing ocean warming and deoxygenation, affecting biodiversity, productivity, and biogeochemical cycling. In coastal sediments, anaerobic organic matter degradation essentially fuels the production of hydrogen sulfide and methane. The release of these compounds from sediments is detrimental for the (local) environment and entails socio-economic consequences. Therefore, it is vital to understand which microbes catalyze the re-oxidation of these compounds under environmental dynamics, thereby mitigating their release to the water column. Here we use the seasonally dynamic Boknis Eck study site (SW Baltic Sea), where bottom waters annually fall hypoxic or anoxic after the summer months, to extrapolate how the microbial community and its activity reflects rising temperatures and deoxygenation. During October 2018, hallmarked by warmer bottom water and following a hypoxic event, modeled sulfide and methane production and consumption rates are higher than in March at lower temperatures and under fully oxic bottom water conditions. The microbial populations catalyzing sulfide and methane metabolisms are found in shallower sediment zones in October 2018 than in March 2019. DNA- and RNA profiling of sediments indicate a shift from primarily organotrophic to (autotrophic) sulfide oxidizing Bacteria, respectively. Previous studies using data collected over decades demonstrate rising temperatures, decreasing eutrophication, lower primary production and thus less fresh organic matter transported to the Boknis Eck sediments. Elevated temperatures are known to stimulate methanogenesis, anaerobic oxidation of methane, sulfate reduction and essentially microbial sulfide consumption, likely explaining the shift to a phylogenetically more diverse sulfide oxidizing community based on RNA.